Geotecnologias como subsídio para gestão costeira: análise dos ciclos erosivos e progradacionais da linha de costa de Icaraí de Amontada - Nascimento, José Victor Sousa (2024)
The erosive and / or progradational processes of a beach quickly modify it, with the coastline being the first feature to be altered by them. Coastal erosion can be caused by several natural and anthropogenic factors, resulting in a retreat from the coastline. From this, the motivation of the present work consists of, from the use of geotechnologies, monitoring the behavior of the coastline of the beach of Icaraí de Amontada between the years 2003 to 2019 to understand its erosive and progradational cycles. It is also sought, based on forecasts for the coastline in the next 10 and 20 years, to contribute to ordering the occupation of the beach, aiming to minimize the losses caused by the erosive processes that are active. The methodology consisted of bibliographic, cartographic survey and field activities. From the processing of Quickbird satellite images, in the ArcGIS 10.5 software with the extension DSAS 5.0, the multitemporal analysis of the variation of the coastline was carried out. The field activities, which took place in 2018 and 2019, included the acquisition of a coastline in situ, for subsequent integration with the data obtained through satellite images, and topographic data from 6 monitoring profiles, with the RTK equipment and data collection sediments in them. An analysis was also carried out related to occupation in the region, observing the increase in the built area between the years 2003 and 2019. From the analysis of the variation of the coastline, it was observed that the beach of Icaraí de Amontada has a character predominantly erosive, with maximum rates reaching -2.23 m / year. It was also seen that it has a sector that is in progradation due to its morphological configuration, obtaining progradational rates of 2.42 m / year. A significant increase in the built area, an increase of about 66397.277 m2 in the region demonstrates the need for coastal planning, mainly considering that, based on forecasts for future coastlines, the beach will remain with erosive tendencies, being then a limit for building area in Icaraí de Amontada is recommended. Monitoring is necessary for better management of the region, seeking to better understand the processes that operate in it and control the unruly progress in buildings.